P2 A clinical pathway for the investigation and follow-up of incidental pineal cysts. Issue 3 (14th February 2019) - Raza-Knight, SR; Mathur, S; Lekka, E
Abstract : Objectives: Pineal cysts (PCs) may be incidentally found on intracranial imaging. They are typically quiescent, benign and asymptomatic. However, imaging alone cannot exclude an underlying pineal malignancy. This study reviewed our hospital's experience of managing PCs in order to develop a clinical pathway to guide their investigation and follow-up. Design: Single-centre retrospective review of cases. Subjects: Patients referred to our hospital with a PC. Methods: Case notes and imaging from patients referred to our hospital with a clinically-coded 'pineal cyst' between 2007 and 2017 were reviewed. Results: 43 cases were included. The most common indication for intracranial imaging was headache (12/43), followed by seizures (4/43). No symptoms were attributable to the PC. Follow-up imaging to monitor the PC was performed in 13/43 cases; in a further 10/43 cases, it was carried out for an indication unrelated to the PC. Follow-up was arranged by the neurosurgical team in 12 cases. Uncertainty about the diagnosis led to an endoscopic biopsy in one case, which confirmed a PC. There was no consistent clinical rationale underlying the decision to undertake follow-up imaging, nor its interval or duration. Conclusions: Clinical practice varied widely for the management of incidental PCs. We propose that all PCs should be investigated with standardised MRI, reported by a neuroradiologist and repeated at 6–12 months. Further follow-up and its duration should be guided by the patient's clinical condition and the radiological features of the PC.